Experiências educacionais renovadas no Estado de São Paulo : análise de práticas escolares do experimental da Lapa (1961-1971) à luz dos movimentos educacionais - Bizzocchi, Carlos Eduardo (2015)
The Primary School called ""Dr. Edmundo de Carvalho"" Experimental School, also known as ¿Experimental da Lapa¿ School, was one of the references in experimental education among the several experiments during the 1960s and 1970s in the State of Sao Paulo, Brazil. From the educational movements which influenced and substantiated the school operations and philosophy we may find Escola Nova (New School), Escola Compensatória (Compensatory School), and Escola Compreensiva e Tecnicismo (Comprehensive School and Technicism). This paper aims at analyzing, from the perspective of educational movements and school practices, both pedagogical and from instructors, and curriculum aspects, during the time in which the school tried the eight-year continuous teaching system, in order to understand the school operation and identification. There is evidence of the new-school influence on the main pedagogical practices, whereas the compensatory school is firmly supported by actions which were developed by the general community, and especially by the students¿ families. Technicism, in turn, was applied in an appropriate and adapted manner. It had arisen from the instructions within the official educational projects, designed by the government during the 1950s, and later on applied during the years of military regime. Comprehensive School fits in the continuous and universal education model that had been claimed since the Second World War, according to which there should be no distinction concerning the quality of teaching during the second cycle (secondary education) regarding students who came from different social classes. Lapa Experimental School might be considered as an institution that was shaped in these models during the time it was studied, when the ¿Experimental da Lapa¿ Core School was established, in order to guide and coordinate the setting up of the eight-year continuous teaching system. This study is based on the accounts of its practices and data which have been collected in other researched papers.